Boesenbergia rotunda (L.) Mansf.: A Review of Phytochemistry, Pharmacology, and Pharmacokinetics - Hop, Nguyen Q.; The Son, Ninh (Current Organic Chemistry, 2023)
Boesenbergia rotunda (the family Zingiberaceae) is a well-known medicinal plant from Southeast Asia and China. Its parts, especially the roots, were used as an alternative in cuisine, and flavoring. Many attempts tend to explore its phytochemistry and pharmacological values. The ultimate goal of this review is to critically offer the pharmacological values and mechanisms of action of B. rotunda crude extracts and their isolated compounds. Phytochemical investigation and pharmacokinetics were also discussed.On the basis of the most effective keyword
Keywords: phytochemistry